Conhecimento dos profissionais de enfermagem sobre as medidas de prevenção de infecção de corrente sanguínea associadas a cateteres venosos periféricos: construção e validação de instrumento - Pelizari, Aline Eloá Barbosa (2019)
Introduction: Bloodstream infections (BSI) are the second leading cause of healthcare-related infections (HAIs) and are considered to be the infection with the greatest preventive potential. Peripheral venous catheters (PVC) are commonly used in health services, their use increase the risk of bloodstream infection and bacteremia, with high associated morbidity and mortality. Objective: To develop and validate an instrument for assessing the knowledge of nursing professionals and students on the prevention measures for BSI associated with PVC. Method: Quantitative study of methodological development. The instrument was developed based on national and international publications and guides. The validation was by face and content. Ten expert judges with professional experience and / or infection prevention and control validated the instrument for clarity and relevance, using a 4-point Likert scale. Items with a content validity index ≥ 0.8 were considered valid. After this stage of validation by expert judges, a pre-test was carried out with 42 professionals, technical students and nursing students. Results: The instrument was built following the logical order of clinical practice, starting from the broadest to the most specific concept, ensuring clarity, objectivity, simplicity, absence of deviations and relevance. During the construction period this was discussed in a research group which made the instrument more refined for sending to expert judges. All items when assessed individually obtained a content validity index greater than 0.90 in relation to clarity and representativeness, ten items were altered in the wording, two items were unified and one item was removed after content validation according to suggestions of the judges, as to the vocabulary and syntax of placement, in order to make the statements more clear, objective and direct. Four items were rewritten after the pre-test in order to facilitate understanding and not be a confusing factor. The final instrument was composed of 34 dichotomous questions. Conclusion: The instrument developed was validated by the judges and the target population (pre-test), represents a major advance in the area of knowledge and is available for use.